Plasma-Enhanced Chemical Vapor Deposition of Indene for Gas Separation Membrane - Myat Kyaw; Shinsuki Mori; Nathaniel Dugos; Susan Roces; Arnel Beltran; Shunsuke Suzuki (ASEAN Journal of Chemical Engineering, 2019)
Polyindene (PIn) membrane was fabricated onto a zeolite 5A substrate by using plasma-enhanced chemical vapor deposition (PECVD) at low temperature. Membrane characterization was done by taking Scanning Electron Microscopy (SEM) and FT-IR measurements and the new peak was found in the plasma-derived PIn film. Membrane performance was analyzed by checking permeability of pure gases (H2, N2, and CO2) through the membrane. PECVD-derived PIn membrane showed high gas barrier properties and selectivities of 8.2 and 4.0 for H2/CO2 and H2/N2, respectively, at room temperature